(untitled) (Research, Society and Development, 2022)
Adolescence is considered an evolutionary stage characterized by growth and biopsychosocial development and comprises the age group from 12 to 16 years, according to the World Health Organization (WHO). In this way, the general objective of the study is to understand the role of psychologists in the care of pregnant adolescents aged between 12 and 16 years. The research methodology was developed based on the descriptors Actuation of the psychologist, Pregnancy in adolescence, Consequences, which were based on a bibliographic method of qualitative analysis, with data search on Google Scholar platforms, Scielo, journals, books and other sources. bibliography according to the proposed theme. Emotional problems such as anxiety, postpartum depression, hormonal changes and changes in goals, somehow impact the life of the pregnant teenager who begins to live with changes in the environment in which she lives. Therefore, the Psychologist has an important role as a preventive action or in helping the teenager and the family in the emotional sphere, in order to contribute to the improvement of the mental aspects, arising from these difficult adaptation moments, which can occur during pregnancy, until the birth of the child.